PENINGKATAN AKTIVITAS DAN KERJA SAMA DALAM KULIAH DRAMA PADA MAHASISWA SEMESTER III PENDIDIKAN BAHASA DAN SASTRA INDONESIA PBS FKIP UNIVERSITAS JAMBI - D., Yusra (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article presents the results of research about Increased Activity and Cooperation of Student in Drama Class of The third Semester of Pendidikan Bahasa dan Sastra Indonesia PBS FKIP UNJA. Methods to increase the activityand cooperation of students, in this study, is a participatory method and the two stay two stray method. The results showed that through the application of these methods, activities and cooperation in student learning can be improved.Keywords: activity and coorperation of student, participatory method, the two stay two stray method